"Out of the Labs": The role for ethnography in guiding clinical trials. Issue 1 (September 2013) - GARGEYA, YOSHA; HOLME, MADS
Abstract : Ethnography and clinical research appear fundamentally disparate, even conflicting. Their very objectives are dichotomous – the latter moves molecules 'from the lab to consumer market' in controlled environments, while the former studies the uncontrolled environment of everyday life. However, with the new reality of pharmaceutical research and development, companies are urged to look into new ways of delivering impact and value to payers, prescribers, and users. This paper explores how ethnographic research can fill that role in early stages of pharmaceutical clinical trials, challenging current paradigms of method as well as parameters for success – and how bridging methodologies can open new avenues for ethnographic practice in business.